2020
DOI: 10.1136/bmjgh-2019-002156
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence among women with and without disabilities: a pooled analysis of baseline data from seven violence-prevention programmes

Abstract: IntroductionIntimate partner violence (IPV) is a serious public health and human rights violation which impacts approximately one in three women worldwide. Some existing evidence suggests that women with disabilities are at higher risk of IPV, but is largely limited in geographical scope to the Global North, and comparison across settings has been hampered by inconsistent measurement of both IPV and disability.MethodsPooled analysis of baseline data from 8549 adult women participating in seven IPV prevention s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…However, it is not yet systematically integrated into IPV prevention research. The majority of What Works research projects included the Washington Group Short Set (WGSS) of questions [70] to assess disability and a pooled analysis of What Works baseline data demonstrated that disabled women were twice as likely to report recent experience of IPV [71]. Of note is that one of the domains assessed in the WGSS is impairment in cognitive function (remembering/concentrating) which is a common symptom of mental health problems, especially PTSD, which may result from experience of violence.…”
Section: Disabilitymentioning
confidence: 99%
“…However, it is not yet systematically integrated into IPV prevention research. The majority of What Works research projects included the Washington Group Short Set (WGSS) of questions [70] to assess disability and a pooled analysis of What Works baseline data demonstrated that disabled women were twice as likely to report recent experience of IPV [71]. Of note is that one of the domains assessed in the WGSS is impairment in cognitive function (remembering/concentrating) which is a common symptom of mental health problems, especially PTSD, which may result from experience of violence.…”
Section: Disabilitymentioning
confidence: 99%
“…The same analysis also showed that the odds of reporting recent IPV increased with increasing severity of disability: women with severe disability reported higher odds of IPV (aOR=2.63; 95% CI: 1.95 to 3.55), as did women with moderate disability (aOR=1.86, 95% CI: 1.57 to 2.21), compared with women without disabilities. 11 Women with disabilities experience increased rates of IPV because the interplay of social, gendered and economic processes associated with stigma towards and discrimination against disabled people which exacerbate their vulnerabilities and limit their options for self-protection. Women with disabilities often have less education, and are therefore poorer, 14 and may have additional out-of-pocket costs for healthcare and adaptive devices expenses, further exacerbating poverty.…”
Section: What Are the New Findings?mentioning
confidence: 99%
“…The obvious advantage was use of a standardised measure and a commonly recommended cut-point designed to yield comparable metrics across diverse settings. 45 While the WG-SS can be used to group participants by severity of disability as we have done elsewhere with some of these data, 11 we lacked the statistical power to compare different levels of disability in these analyses. Differentiating programme impact by severity of disability when possible would benefit future work in this area.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is a paucity of data documenting the different subforms of IPV experienced by people with disabilities, with few studies on how disability status is associated with experiences of psychological abuse, controlling behaviors, and economic abuse. 10,23 This is a significant gap because these forms of IPV are highly prevalent in people without disabilities. 24,25 The 2019 New Zealand Family Violence Survey provided an opportunity to address these information gaps.…”
Section: Introductionmentioning
confidence: 99%